GREEN INVESTMENT, DIGITAL TECHNOLOGY AND DIGITAL FINANCE CAPABILITY ON FINANCIAL SUSTAINABILITY - Debbi Chyntia Ovami; Sari Wulandari; Junita Putri Rajana Harahap; Noor Marini Haji Abdullah; Noreen Azella Nawi; Suci Agsani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to examine the role of Digital Finance Capability (DFC) in moderating the influence of green investment and digital technology on the financial sustainability of MSMEs. MSMEs, which play an important role in the Indonesian economy, often face obstacles in accessing technology and financing that can support financial sustainability. The method used in this study is a quantitative approach with a survey of MSMEs that have utilized digital technology and green investment. Primary data will be collected through a questionnaire distributed to MSME actors. The analysis technique used is Structural Equation Modeling (SEM) to test the relationship between the variables studied. The results of the study show that green investment does not have a significant effect on financial sustainability, while digital technology and digital finance capabilities have an effect on financial sustainability. Digital finance capabilities cannot moderate the influence of green investment and digital technology on financial sustainability.